Teeny Weenies: The Intergalactic Petting Zoo and Other Stories - Lubar, David; Mayer, Bill (Illustrator) (New York Tom Doherty Associates, 2019)
A selection of twelve stories about aliens, a community pool filled with bullies, a surprising start to the Fourth of July fireworks, and other peculiar things, with comic- book style illustrations.
"A Starscape Book."
Keywords: Zoos; Juvenile fiction; Bullies; Juvenile fiction; Zombies; Juvenile fiction; Childrens stories, American; Paranormal fiction; Short stories; Fiction